2018
DOI: 10.17755/esosder.341663
|View full text |Cite
|
Sign up to set email alerts
|

Okul Müdürleri̇ni̇n Paternali̇st Li̇derli̇k Davranişlarinin İncelenmesi̇

Abstract: Bu araştırmanın amacı, kamu ortaokullarında görevli öğretmenlerin kendi okul müdürlerinin paternalist liderlik davranışlarına ilişkin algılarının nasıl olduğunu saptamaktır. Araştırma, betimsel tarama modelinde yapılmıştır. Araştırmanın örneklemini, 2016-2017 eğitim-öğretim yılında Mardin il merkezinden basit seçkisiz örnekleme yöntemi ile seçilen 20 ortaokul ve bu okullarda görevli 261 öğretmen oluşturmaktadır. Araştırmanın verileri, Dağlı ve Ağalday (2017) tarafından geliştirilen "Okul Müdürlerinin Paternali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…According to this finding, it can be said that teachers generally evaluate their principals with fatherly leadership qualities. This result reveals the idea that principals have a helpful profile towards teachers, they tend to deal with almost every problem and care about loyalty, as stated in similar studies (Dağli & Ağalday, 2018;Köksal, 2011). Another finding in this study is that the effect of gender on paternalist leadership assessments is not significant.…”
Section: Change Of Teachers' Paternalist Leadership Perceptions By Gender Age and Year Of Studysupporting
confidence: 76%
See 1 more Smart Citation
“…According to this finding, it can be said that teachers generally evaluate their principals with fatherly leadership qualities. This result reveals the idea that principals have a helpful profile towards teachers, they tend to deal with almost every problem and care about loyalty, as stated in similar studies (Dağli & Ağalday, 2018;Köksal, 2011). Another finding in this study is that the effect of gender on paternalist leadership assessments is not significant.…”
Section: Change Of Teachers' Paternalist Leadership Perceptions By Gender Age and Year Of Studysupporting
confidence: 76%
“…This finding is consistent with the findings of some research conducted for teachers (Cerit et al, 2011;Koç & Alpullu, 2019). However, in other studies, it is stated that the gender variable significantly affects the perception of paternalist leadership and that men have a higher perception (Dağli & Ağalday, 2018). In the study, it was determined that the variables of age and working year did not significantly differentiate teachers' paternalist leadership perceptions.…”
Section: Change Of Teachers' Paternalist Leadership Perceptions By Gender Age and Year Of Studymentioning
confidence: 79%
“…On the other hand, teachers' perception of the paternalist leadership style of school principals who act as family members, authoritarian, and have good relationships is low when compared to other leadership styles. While Özgenel and Dursun (2020) determined school administrators' paternalist leadership behaviors at a "moderate" level, according to perceptions of teachers, Dağlı and Ağalday (2018) and Aktaş (2019) concluded that the perception of paternalist leader behaviors among school principals was higher.Some studies (Çetinkaya, 2011;Gündüz & Doğan, 2009;Kazancı, 2010;Özcan 2013) revealed that school principals display the transformational leadership style at the highest level according to teachers' perceptions. Smith (2008), Günay Süle (2019), and Ankaralıoğlu (2020) found in their studies that spiritual leaders make decisions by considering their strong moral convictions and what is best for the organization.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In parallel with the studies above, there are some studies which suggest that a paternalistic leadership style is one of the appropriate leadership styles for the cultural norms of Turkish society and that it has positive effects with regard to citizenship, intimidation and cynicism 558 in schools. These studies found that school principals displayed paternalistic leadership qualities frequently (Dağlı and Ağalday, 2018;Cerit, 2012;Cerit, 2013;Cerit et al, 2011;Mete and Serin, 2015;Aydıntan, 2016). Although there are intercultural comparative studies on educational leadership, there is a need for an in-depth analysis of school principals' leadership implementation in different countries in the context of different cultures (Harris, 2016;Ghamrawi, 2011).…”
Section: Introductionmentioning
confidence: 99%